Influence of Perceived Coercion and Motivation on Treatment Completion and Re-Arrest among Substance-Abusing Offenders - Prendergast, Michael (2008)
The effects of perceived coercion and motivation on treatment completion and subsequent rearrest were examined in a sample of substance-abusing offenders assessed for California's Substance Abuse and Crime Prevention Act (SACPA) program. Perceived coercion was measured with the McArthur Perceived Coercion Scale; motivation was measured with the subscales of the Stages of Change Readiness and Treatment Eagerness Scale (SOCRATES). At treatment entry, clients were more likely to believe that they had exercised their choice in entering treatment than that they had been coerced into treatment. SACPA clients scored relatively low on Recognition and Ambivalence regarding their drug use but relatively high on Taking Steps to address their drug problem. Correlations between perceived coercion and motivation measures at treatment entry indicated that these are separate constructs. In logistic regression models, the Recognition subscale of the SOCRATES significantly predicted “any re-arrest,” and Ambivalence and Taking Steps predicted “any drug arrest.”